PENGARUH ORGANISASI PERSAUDARAAN SETIA HATI TERATE DALAM MENUMBUHKAN KARAKTER DISIPLIN DI RAYON DESA BANGKO MAKMUR KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Siti Qoriah; Ahmad Eddison; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was motivated by the researcher's desire to analyze the influence of organization persaudaraan setia hati terate in fostering the disciplined character in bangko makmur village bangko pusako district rokan hilir regency. The aim of the study is to know how the influence of the organization persaudaraan Setia Hati terate in fostering the Disciplined Character in Bangko Makmur Village District, Bangko Pusako District, Rokan Hilir Regency. This research is a quantitative descriptive research which has conducted in Bangko Makmur village from July 2020 to November 2020. The population in this study were all members of organization persaudaraan setia hati terate which totaled 41 people with the sampling method in the form of total sampling. The data collection techniques used were observation, interviews , questionnaires and documentation. The data analysis technique used was descriptive quantitative. The organization persaudaraan setia hati terate in cultivating disciplined characters in bangko makmur village is very good. There is a significant influence between the organization persaudaraan setia hati terate in fostering disciplined characters in bangko makmur village. So the hypothesis in this study is accepted, based on the results of the calculations above, it is known that the coefficient of determination (R square) is 0.222, which means that the influence of the in dependent variable (PSHT organization) in growing the dependent variable (Discipline Character) is 47.2% . Thus it can be concluded that there is an influence of the organization persaudaraan setia hati terate in growing discipline characters in rayon bangko makmur village bangko pusako district rokan hilir regency.Key Words: Influence, Organization, Persaudaraan Setia Hati Terate, Discipline,Characters.